Bone marrow mesenchymal stem cell-derived extracellular vesicles improve the survival of transplanted fat grafts - Huang, He (Mol Med Rep, 2017)
Autologous fat grafting is a promising surgical technique for soft tissue augmentation, reconstruction and rejuvenation. However, it is limited by the low survival rate of the transplanted fat, due to the slow revascularization of such grafts. Previous studies have demonstrated that bone marrow mesenchymal stem cell-derived extracellular vesicles (BMSC-EVs) are proangiogenic. The present study aimed to investigate whether BMSC-EVs could improve the survival of transplanted fat grafts. Extracellular vesicles were isolated from the supernatant of cultured rat bone marrow mesenchymal stem cells, and characterized by flow cytometry and scanning electron microscopy. Their proangiogenic potential was measured in vitro using tube formation and cell migration assays. Subsequently, human fat tissue grafts, alongside various concentrations of BMSC-EVs, were subcutaneously injected into nude mice. A total of 12 weeks following transplantation, the mice were sacrificed and the grafts were harvested. The grafts from the experimental group had a higher survival rate and an increased number of vessels compared with grafts from the control group, as demonstrated by tissue volume, weight and histological analyses. Reverse transcription-quantitative polymerase chain reaction analysis indicated that the expression levels of proangiogenic factors were increased in the experimental group compared with in the control group, thus suggesting that BMSC-EVs may promote neovascularization by stimulating the secretion of proangiogenic factors. The present study is the first, to the best of our knowledge, to demonstrate that supplementation of fat grafts with BMSC-EVs improves the long-term retention and quality of transplanted fat.